Emirates consensus recommendations on cardiovascular risk management in type 2 diabetes - Sabbour, Hani; Almahmeed, Wael; Alawadi, Fatheya; Shehab, Abdullah; Al Zubaidi, Abdulamjeed; Bashier, Alaaeldin; Ghulam, Abdul Rauf; Rashid, Fauzia; Zaky, Hosam; Heshmat Kassemn, Hussien; Adi, Jamila Bin; Tahir, Juwairia; et al. (Frontiers in Endocrinology, 2025)
Background The combination of cardiovascular disease and diabetes is a highly prevalent condition in the United Arab Emirates. Development and dissemination of evidence-based regional recommendations for optimal screening, treatment and referrals of people with diabetes and high cardiovascular risk is an important priority. Consensus panel An expert panel of diabetologists, endocrinologists and cardiologists from the Emirates Cardiac Society and Emirates Diabetes and Endocrine Society as well as different entities in the UAE, discussed and reviewed evidence and also a consensus report from the American Diabetes Association to formulate contextualized recommendations that could be applied for optimal management of cardiovascular risk in people with diabetes in the UAE. Consensus findings The combination of heart failure and other cardiovascular risks is a highly prevalent finding among people with diabetes in the United Arab Emirates. The causal inter-relationships between diabetes and heart failure are multifactorial and regular assessments of symptoms and steps for mitigation of risk factors are an important priority. The universal definition and classification of heart failure provides a useful framework for recommending optimal screening, treatment, and referral strategies to diabetic individuals at various stages of the cardiovascular continuum. Routine measurement (at least yearly) of natriuretic peptides and high-sensitivity troponins can help identify patients requiring cardiac imaging referrals. However, recommending routine measurements of natriuretic peptides and/or high-sensitivity troponins to all diabetic individuals must balance clinical judgment and cost implications. While SGLT2i must be an important part of the standard of care, insulin, GLP1 receptor agonists and/or metformin can be useful for additional glycemic control. Conclusion The consensus panel hopes that the recommendations presented herein can offer guidance for optimal screening, treatment and referral of people with a concomitance of diabetes and high cardiovascular risk in the United Arab Emirates.